KOMPETENSI WARTAWAN DALAM MENULIS BERITA PADA MEDIA ONLINE KOMPAS.COM - Prima Hanifah, - (2019)
Journalist profession is a profession that represents the ears, eyes, and mouth of the public. Journalists are required to be able to produce information that is reliable, accurate, independent, objective and unbiased. The values borne by journalists are contained in the Journalistic Code of Ethics which is the basis for a journalist in carrying out journalistic activities. The media that houses a journalist is trying to establish various types of qualifications in the recommendations of prospective journalists. This research aims to measure the competence of journalists in writing news on online media Kompas.com. The concepts used are journalist competency, news writing, and online media while the theory used is the normative media theory. The methodology research is quantitative. The characteristic of the research is descriptive. The type of research conducted in the survey method. The population of this research is 42 journalists working in online media Kompas.com with sampling techniques, namely census. Data processing was carried out using SPSS version 21 resulting in the assessment category of journalist competency variables as many as 41 respondents in the 62- 82 category with a high category which meant showing the competence of kompas.com journalists in writing news into a high category. The conclusion of this research show that with S1 qualifications all majors set by Kompas.com to become a journalist, do not affect Kompas.com journalists to work in accordance with the applicable journalistic code of ethics, whether journalists majoring in Communication Studies or Non-Communication Studies